PERAN ACCOUNT OFFICER PADA PT. BANK BJB KANTOR CABANG PEMBANTU KEBAYORAN LAMA - Muhammad Iqbal Akbary (2021)
To market credit at a bank, there is a section called the Account Officer, which is the section that manages credit marketing until the credit is disbursed by the customer. Explain the things that an Account Officer does in increasing bank income. Explain the things that an Account Officer does in increasing bank income. The Account Officer is tasked with finding suitable customers, in accordance with the criteria for bank assessment regulations which will later be analyzed and proposed the amount of credit lending. An Account Officer has a target of achieving credit distribution every year. The credit achievement target of each branch of Bank BJB is different, this is due to the geographical factor of the bank's location so that the achievement target is determined by several regional offices. An Account Officer's effort in finding customers is to do a credit analysis to ensure the eligibility of prospective customers or before a credit loan is given. Based on the role of the performance improvement strategy or the Account Officer achievement target at the BJB KCP Kebayoran Lama bank, currently the BJB KCP Kebayoran Lama bank has not achieved its sales target, because the NPL value at the bank is currently exceeding the percentage limit of the NPL value.